Meningkatkan Hasil Belajar Menggunakan Alat Permainan Puzzle Pada Materi Operasi Hitung Campuran Bilangan Bulat Kelas IV SD Negeri Pogo Lede - Wada, Marselina; Making, Samuel Rex M; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The cause of the problem of low learning outcomes for fourth grade students at Pogo Lede State Elementary School in mathematics subjects consists of teacher and student foctors. Teachers are less creative in delivering material, do not use media that, can attract students’ attention and interest in learning, focus more on using prinred books, and do not involve students. Apart from that, he also has difficulty in calculating. This makes students feel bored, fed up and sometimes students just sit still during the learning process so that the material provided by the teacher cannot be received optimally, causing the learning outcomes of class IV students at SD Negeri Pogo Ledeto still be below average. This research uses classroom action research (PTK) techniques because the research is carried out to solve problems that occur in the claasroom. In classroom action research improvements are carried out gradually and continuously as long as the research activities are carried out. Therefore, in PTK there is an implementation cycle in the from of a planning pattern. Carrying out observations and reflections so that in the next dycle it reaches the level you want to achieve. Based on the background above, the researcher chose to apply the puzzle game learning method. This method can make students activel discuss in class or in small groups to formulate the title improving learning outcomes using puzzle game tools on operation material counting mixed integers class IV Pogo Lede State Elementary School